Salinity induced effects on the growth rates and mycelia composition of basidiomycete and zygomycete fungi. (December 2017) - Venâncio, C.; Pereira, R.; Freitas, A.C.; Rocha-Santos, T.A.P.; da Costa, J.P.; Duarte, A.C.; Lopes, I.
Abstract: Soil salinization, as the combination of primary and secondary events, can adversely affect organisms inhabiting this compartment. In the present study, the effects of increased salinity were assessed in four species of terrestrial fungi: Lentinus sajor caju, Phanerochaete chrysosporium, Rhizopus oryzae and Trametes versicolor . The mycelial growth and biochemical composition of the four fungi were determined under three exposure scenarios: 1) exposure to serial dilutions of natural seawater (SW), 2) exposure to serial concentrations of NaCl (potential surrogate of SW); and 3) exposure to serial concentrations of NaCl after a period of pre-exposure to low levels of NaCl. The toxicity of NaCl was slightly higher than that of SW, for all fungi species: the conductivities causing 50% of growth inhibition (EC50 ) were within 14.9 and 22.0 mScm −1 for NaCl and within 20.2 and 34.1 mScm −1 for SW. Phanerochaete chrysosporium showed to be the less sensitive species, both for NaCl and SW. Exposure to NaCl caused changes in the biochemical composition of fungi, mainly increasing the production of polysaccharides. When fungi were exposed to SW this pattern of biochemical response was not observed. Fungi pre-exposed to low levels of salinity presented higher EC50 than fungi non-pre-exposed, though 95% confidence limits overlapped, with the exception of P. chrysosporium . Pre-exposure to low levels of NaCl also induced changes in the biochemical composition of the mycelia of L. sajor caju and R. oryzae, relatively to the respective control. These results suggest that some terrestrial fungi may acquire an increased tolerance to NaCl after being pre-exposed to low levels of this salt, thus, suggesting their capacity to persist in environments that will undergo salinization. Furthermore, NaCl could be used as a protective surrogate of SW to derive safe salinity levels for soils, since it induced toxicity similar or higher than that of SW. Graphical abstract: Highlights: Effects of increased salinity were studied in four species of terrestrial fungi. NaCl revealed to be a protective surrogate for seawater at early stages of soil risk assessment. Fungi are capable to cope with increased salinity for prolonged exposure periods. Exposure to NaCl, but not seawater, increased the production of some metabolites.